Road Maintenance Planning of the Fier-Vlore Road Axis, based on the Assessment and Forecast of AADT and Los Service Level - Arian Lako; Shkelqim Gjevori (Qubahan Academic Journal)
The relevance of this study lies in the fact that maintaining roads in good condition is an important condition for ensuring the safety and comfort of road traffic, as well as the economic development of the region. The aim of the study is to develop a method for planning road maintenance along the Fier-Vlore axis based on the assessment and forecast of the level of service AADT and LOS in order to improve the quality and safety of road traffic. The AADT and LOS service level estimation and forecast method is used to determine the performance of road networks and identify problem areas. The results of this study indicate that in the next 10 years, the level of service on this section of the road will be satisfactory and will be classified as “C”. However, after 2027 until 2032, the service level is expected to decline to category “D” and “E”, which could potentially lead to restrictions in manoeuvring and an increase in traffic accidents. In addition to reducing the distance, the construction of this Fier-Vlore Road has a significant impact both in reducing transport costs and in reducing the stress and anxiety caused by the old road. The main goal of the road is to provide comfort, safety, minimum cost and sustainability to the environment. In general, the use of the AADT and LOS Service level estimation and forecast method has significant practical value for planning investments in road maintenance and road infrastructure improvement.